Review on the suppression of Zn dendrite for high performance of Zn ion battery - Abdulla, J; Cao, J; Wangyao, P; Qin, J (Journal of Metals, Materials and Minerals, 2020)
Researchers are paying more attention to the environmentally friendly and low-cost energy storage devices, due to the environmental issues and energy crisis caused by current commercial energy storage technologies. Zinc ion battery (ZIB) is one of the new, environment-friendly and low-cost energy storage technologies, which is the most promising alternative technology to replace the lithium ion battery applications. However, one of the challenges-dendrite growths during cycling of Zn anode is still limited its practical applications. In this review, the recent progress on suppression of Zn dendrite in various electrode design, electrolyte additives, and separator modifications for ZIBs is summarized. Â